Magnesium and Ketamine Gargle and Postoperative Sore Throat - Teymourian, Houman (Anesth Pain Med, 2015)
BACKGROUND: Postoperative sore throat is one of the most common complications after endotracheal intubation. Both Ketamine and magnesium can block N-methyl-D-aspartic acid (NMDA) receptors and provide central and local analgesia. OBJECTIVES: To compare the effect of magnesium sulfate and ketamine gargle on the incidence and severity of postoperative sore throat. PATIENTS AND METHODS: A total of 100 patients candidate for emergency acute appendicitis surgery were enrolled in the study. Patients in ketamine group received ketamine gargle (0.5 mg/kg) and magnesium group received magnesium sulfate gargle (20 mg/kg up to 30 mL dextrose water 20%) 15 minutes before the operation. Patient complaint of postoperative sore throat, and its severity measured by visual analogue scale (VAS) were recorded at baseline in recovery room, and then 2, 4, and 24 hours after operation. RESULTS: There were no significant differences between age, sex, and body mass index (BMI) between two groups of patients. Hemodynamics of patients, including blood pressure, respiratory rate, oxygen saturation %, and conscious state were not significantly different (P > 0.05). Number of patients with sore throat were significantly lower in magnesium group compared to ketamine group at 2 (P = 0.032), 4 (P = 0.02), and 24 hours (P = 0.01) after the operation. Sore throat pain score (VAS) was significantly lower in magnesium group compared to ketamine group at 2 (P = 0.019), 4 (P = 0.028), and 24 hours (P = 0.014) after the operation. CONCLUSIONS: Magnesium at low dose decreases sore throat and pain severity more effectively compared to ketamine gargle.